2013
DOI: 10.1118/1.4815593
|View full text |Cite
|
Sign up to set email alerts
|

WE‐E‐141‐02: An Improvement in IMRT QA Results and Beam Matching in LINACs Using Statistical Process Control

Abstract: Purpose: The purpose of this study is to apply the principles of Statistical Process Control (SPC) in the context of patient specific IMRT QA to set clinic specific action limits and evaluate the impact of changes to the MLC calibrations on IMRT QA results. Methods: Ten months of IMRT QA data with 247 unique QAs collected on three beam matched LINACS were retrospectively analyzed with a focus on the Gamma Pass Rate (GPR) and the average ratio between the measured and planned doses. Initial control charts and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, this output factor is not the main parameter for adjustment among the LINACs. The output factor data can be adjusted manually at the TPS, in accordance to the modeling that has been obtained [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this output factor is not the main parameter for adjustment among the LINACs. The output factor data can be adjusted manually at the TPS, in accordance to the modeling that has been obtained [8].…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of the beam matching concept to several LINACs should be accompanied by adequate maintenance and Quality Assurance (QA) processes, to ensure the suitability of dosimetry parameters among the LINACs. There is a published paper discussing QA in beam matched LINAC for several tumor case data [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers were reported about the performance of beam-matched linear accelerators (Kairn et al, 2015;Bhangle et al, 2011). Gagneur and Ezzell (2013) and Xu et al, (2019) reported the patient's specific quality assurance of VMAT, SBRT/SRT for beam-matched linear accelerators. To the best of our knowledge, we could not find any study-related to the surface dose measurement for beam-matched linear accelerators.…”
Section: Verification Of Surface Dose For Flattening Filter and Flattening Filter Free Beams In Beam-matched Medical Linear Acceleratorsmentioning
confidence: 99%